Extrapolation of professional judgment in the accounting system: significance and impact on development - Kundrya-Vysotska, Oksana; Vagner, Iryna; Demko, Iryna (Herald of Economics, 2023)
Introduction. In the process of making important management decisions, the professional judgment of the accounting specialist is decisive. The novelty of such an object as the professional judgment of an accounting specialist requires research for trend changes, effectiveness, risks of its extrapolation, which have an impact on the development of the accounting system, business, and the accounting profession itself.The purpose of the study is to examine the criteria and prerequisites for the practical application of the professional judgment of an accounting specialist and its effectiveness in the context of extrapolation in the accounting system, in the economic activity of the economic entity, in the development of the accounting profession.Methods. In the process of researching the prerequisites for applying the accountant’s professional judgment, general scientific methodological techniques were used, in particular induction and deduction. Structural-logical and semantic analysis - to clarify the risks associated with the implementation of professional judgment, as well as the possible negative impact on the practice of making such decisions. Grouping and classification - to justify the criteria of effective information based on the professional judgment of an accounting specialist.The information base of the research consists of the works of domestic and foreign scientists on the issues of necessity, prerequisites and results of extrapolation of professional judgment, materials of international scientific and practical conferences, results of personal experience and observations.Results. The conditions of application of the accountant’s professional judgment are outlined. The scientific plane of forming professional judgment is characterized, which involves serious training of a specialist according to modern international approaches based on the international code of ethics of professional accountants, which is a model for the development of national ethical and professional recommendations. The results of the extrapolation of professional judgment in the accounting system, in the economic activity of the business entity, and in the development of the accounting profession are analyzed.The risks associated with the implementation of professional judgment are analyzed, as well as the possible negative impact on the practice of making such decisions, on the basis of which the need for further development is outlined, based on which a logical sequence prevails between the principles, standards of accounting and reporting, and the current regulatory and methodological regulation accounting and financial reporting in Ukraine and the professional judgment of accounting specialists.Perspectives. It is expedient to carry out further scientific research in the direction of expanding the scientific and methodical plane of studies regarding the effectiveness of the extrapolation of professional judgments.